Effective Drug Procurement Planning in Hospital Pharmacy Installation: Evaluation and Recommendations - Rista Afriani Fauzia Afriani; Chriswardani Suryawati; Septo Pawelas Arso (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Drug management is a process of planning, implementation, and control. This study evaluates the drug procurement planning process at the Pharmacy Installation of X General Hospital. The research is descriptive qualitative. Data for this study were collected in November 2023, at X General Hospital. The informants in this study consisted of 5 individuals, 2 primary informants, the Head of the Pharmacy Installation and the Pharmacy Warehouse Pharmacist, and 3 triangulation informants, a user, a finance staff member, and the Deputy Director. Data collection techniques included indepth interviews, direct observation (IFRS) with note-taking, and document analysis using monthly drug usage reports. The triangulation method was also applied. Data were analyzed through data reduction, data display, and conclusion drawing. The results revealed that the drug planning process, drug selection, and drug calculation were different from holds. Price determination during planning was based on prices offered by suppliers by cooperation agreements. Examination of financial records showed that the percentage of capital funds in 2023 was 20.7%, indicating that the allocation of funds was inefficient. The number of drug items held at the Hospital, compared to those planned for 2023, was 91.8%, meaning not all drugs were acquired as planned. Similarly, the percentage of drug receipts relative to the plan was also 91.8%, further indicating that not all drugs were received as expected. This study concludes that drug planning and procurement at X General Hospital must still comply with existing regulations, necessitating planning, procurement, and evaluation improvements. The ABC-VEN method can be utilized to assist hospitals in creating a matrix to plan drug procurement more effectively Keywords: Pharmacy, Management, Medicine, Hospital